The Influence Of Digital Accounting On Cashier Performance In The Canteen Umkm Untag Surabaya - Deby Shintawulan Fransiska; Mirana Lavenia; Dika Candra Laili (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
He University of 17 August 1945 Surabaya is one of the universities that has a large number of students, lecturers and employees. It is not uncommon for sellers in the cafeteria to find it difficult to make transactions and errors often occur in calculating the number of transactions because they are still done manually. In this research, a payment system has been developed that uses the Bakoel POS application. Bakoel POS will utilize sensors to read data that will assist in the transaction process. Bakoel POS application design for the canteen payment system. This application is designed as a transaction process in the canteen. Transactions in the canteen include ordering and payment processes. It can be concluded that the Canteen Digital Accounting System Using the Bakoel POS Application has been designed to make it easier for canteen keepers in carrying out the sales process and can increase time efficiency in making transactions. From the test results, it can be seen that this application functions well for the efficiency of payment transactions at the Surabaya Untag canteen cashier.